The story of Rufino slavery, freedom, and Islam in the Black Atlantic - Reis, João José 1952-; Gomes, Flávio dos Santos 1964-; Carvalho, Marcus J. M. de 1957- (Oxford scholarship online, 2019)
'The Story of Rufino' reconstructs the lively biography of Rufino José Maria, set against the historical context of Brazil and Africa in the nineteenth century, that sheds light on slavery and the slave trade, manumission, the complexities of slavery and freedom in Brazil, African freed persons, and the resilience of ethnic and religious identities